Quality of pathologic response and surgery correlate with survival for completely resected bladder cancer following neoadjuvant chemotherapy - Sonpavde, Guru (2009)
BACKGROUND: In a retrospective study of SWOG-S8710/INT-0080 (radical cystectomy [RC] alone vs 3 cycles of MVAC neoadjuvant chemotherapy [NC] before RC for bladder cancer), factors associated with improved overall survival (OS) included pathologic complete response (pCR) defined as P0, treatment with NC, completion of RC with negative margins and ≥10 pelvic lymph nodes (LNs) removed. METHODS: We used stratified Cox regression to retrospectively study the association of quality of pathologic response post-RC with OS in the subset of S8710 patients that received NC and RC with negative margins. RESULTS: Of 154 patients who received NC, 68 (44.2%) were <P2 (P0, Pa, P1, or CIS) at RC, 46 (29.9%) were P0, and the remainder had P2+ disease or did not undergo RC. In 115 patients who had RC with negative margins, compared to P0 patients, those with residual Pa, P1 or CIS appeared to have worse OS (p=.054); OS was significantly worse for residual P2+ (p=.0006). LN+ disease was associated with worse OS than LN- (p=.0005). In patients with LN- disease, those with <10 nodes removed appeared to have inferior OS compared to 10+ nodes (p=.079). The combination of pre-NC clinical stage and post-RC pathologic stage was predictive of OS (p<.0001). CONCLUSION: NC and RC with negative margins for bladder cancer followed by pathological P0 and LN- disease correlate with improved OS. A combination of baseline clinical stage and post-RC pathologic stage may better predict OS.